Holiday Price Rigidity and Cost of Price Adjustment - Daniel Levy; Georg Müller; Haipeng (Allan) Chen; Mark Bergen; Shantanu Dutta (Economica, 2010)
The Thanksgiving–Christmas holiday period is a major sales period for US retailers. Due to higher store traffic, tasks, such as restocking shelves, handling customers' questions and inquiries, running cash registers, cleaning and bagging, become more urgent during holidays. As a result, the holiday-period opportunity cost of price adjustment may increase dramatically for retail stores, which should lead to greater price rigidity during holidays. We test this prediction using weekly retail scanner price data from a major Midwestern supermarket chain. We find that, indeed, prices are more rigid during holiday periods than non-holiday periods. For example, the econometric model we estimate suggests that the probability of a price change is lower during holiday periods, even after accounting for cost changes. Moreover, we find that the probability of a price change increases with the size of the cost change, during both the holiday as well as non-holiday periods. We argue that these findings are best explained by higher price adjustment costs (menu cost) the retailers face during the holiday periods. Our data provides a natural experiment for studying variation in price rigidity because most aspects of market environment such as market structure, industry concentration, the nature of long-term relationships, contractual arrangements, etc. do not vary between holiday and non-holiday periods. We, therefore, are able to rule out these commonly used alternative explanations for the price rigidity, and conclude that the menu cost theory offers the best explanation for the holiday period price rigidity.
Keywords: E12; E31; L16; L11; M31; 330; Price Rigidity; Cost of Price Adjustment; Menu Cost; Holiday Period; Asymmetric Price Adjustment; Monetary Policy